From 'Deviant Girl' to 'Unempowerable Woman': Reconstructing Resistance in the Case of Ashley Smith - LeBlanc, Nicole (Université d'Ottawa / University of Ottawa, 2012)
This research explores the traditional and contemporary construction of undesirable female behaviour as both ‘risky’ and ‘abnormal’, and the implication this had on the Correctional Service of Canada’s response to Ashley Smith’s self-injurious behaviour. Smith was kept in segregation for 11.5 months of federal custody until she ultimately ended her own life while correctional staff watched without intervening. In order to capture the evolution of Smith’s undesirable behaviour and the institutional responses leading up to her death, this thesis begins with an examination of her experiences prior to her confinement in federal prison. This research offers a feminist reading of self-injury and the use of segregation and an in-depth critical examination of the systemic factors that influenced Smith’s self-injury. In order to gain a thorough understanding of Smith’s experiences and how they are systematically situated, a qualitative content analysis was conducted of all public documentation of her case released by the Correctional Service of Canada (CSC), the Office of the Correctional Investigator (OCI), and the Office of the Ombudsman and Child Youth Advocate, as well as federal correctional policies related to segregation, self-injury, institutional transfers, use of force, and use of restraints. Findings suggest that the therapeutic-risk logic adopted by the CSC and OCI to ‘make sense’ of Smith’s undesirable behaviour, led to the reconstruction of Smith’s self-injurious behaviour as both ‘abnormal’ and ‘risky’, rather than as a response to her oppressive correctional environment. This reconstruction ultimately legitimized the perpetual disciplinary and governmental responses Smith endured (e.g. segregation, use of restraints and force, involuntary transfers, involuntary therapeutic injections), which then worsened her behaviour in a cyclical pattern. Reliance on therapeutic-risk logic in different social institutions (the school, hospital and prison) trapped Smith in a carceral network that ultimately responsibilized her for her own victimization and punishment. While it was arguably the collective carceral response that exacerbated Smith’s undesirable behaviour, findings suggest that it was ultimately the extreme disciplinary and governmental forces exerted in the federal prison system that led to her ultimate death. While this research provides ample evidence to support this conclusion, the CSC ultimately silences the gendered injustice in which Smith endured by denying responsibility for her experiences, while disciplacing it onto frontline staff, the medical system, the lack of institutional resources and Smith herself by normalizing her death as merely one of many that remain ‘unpreventable’ within the Canadian prison system.